Intergenerational space / edited by Robert M. Vanderbeck and Nancy Worth. - Vanderbeck, Robert M.; Worth, Nancy (Routledge studies in human geography, 2015)
This title offers insight into the transforming relationships between younger and older members of contemporary societies. The chapter selection brings together scholars from around the world in order to address pressing questions both about the nature of contemporary generational divisions as well as the complex ways in which members of different generations are (and can be) involved in each other's lives.